Effectiveness of Eleovit Preparation with Tissue Preparations in Calves - Azamovich, Kholikov Abror; Abdullaevch, Nurullaev Alisher; Tolkinovich, Khatamov Tolmas (European Journal of Life Safety and Stability (2660-9630), 2021)
The use of the vitamin preparation Eleovit and tissue preparations in the diet of calves optimizes metabolic processes, resulting in more efficient feed consumption and increased production, with a 20.3 % increase in live weight growth.